Risk management of logistics outsourcing risks within the fast-moving consumer goods sectors in China - Wang, Rui-Jie (2020)
As more and more companies choose to outsource logistics, several problems arise. In the short term, logistics outsourcing risks affect the interests and rights of the company, creating problems of information asymmetry and information leakage, hurting the company’s reputation and leading to a gradual loss of control over the outsourced logistics. These risks can be avoided, however, with a sound risk prevention mechanism and risk management measures that inform a strict selection of the third-party logistics company. Companies that are considering outsourcing should consider that in the long term, decreasing consumer satisfaction could lead to a decline in company performance. Despite the importance of this topic, scholars have not examined the consequences of logistics outsourcing risks from the consumers’ perspective. Thus, this research aimed to investigate how logistics outsourcing risks affect consumer satisfaction, delineate the parties responsible for each identified risk and make recommendations for effective risk management strategies for logistics outsourcing in the fast-moving consumer goods sector. Data were obtained from a questionnaire administered to consumers who had purchased fast-moving consumer goods and interviews with employees of companies in this sector.